Praktik Manajemen Pendidikan Mahasiswa Jurusan Administrasi Pendidikan: Kajian Proses dan Hasil - Maisyaroh Maisyaroh (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1998)
The Internship Program of Educational Management Attended by Students of Educational Administration Department: Study of the Process and the Product. The purpose of the study was to investigate the effectiveness of the internship program attended by the students of Educational Administration Department. The data were collected through observation and documentation and were then analyzed in order to get the mean value and the standard deviation. The findings, which concerned the internship process and its products, indicated that the quality of this internship program was categorized good with a relatively homogeneous variation.